Tindak Pidana Pencemaran Laut Akibat Tumpahan Di Balikpapan Dalam Perspektif Hukum Pidana Lingkungan - Yulianor Abdi (Jurnal Penegakan Hukum Indonesia, 2022)
The Panamanian-flagged ship MV Ever Judger, whose captain and the crew were all Chinese nationals, crashed into a pipeline belonging to PT Pertamina Refinery Unit 5 Balikpapan, breaking the pipe and dragging the ship, causing contamination of the sea by the oil. Because of this incident, we are interested in discussing: (1) How is the criminal responsibility for the perpetrators of the marine pollution due to oil spills? (2) Who is responsible for the oil spill case in Balikpapan? This research uses normative research methods. The results and discussion concluded: First, criminal liability is not only applied for individuals in that Ship but also to the corporations. Second, the application of the law regarding criminal acts of environmental pollution contains in-laws and regulations relating to environmental protection and management.  The criminal provisions regarding environmental pollution exist in chapter XV regarding the criminal provisions of Act 32/2009. Regarding criminal sanctions for criminal acts of environmental pollution contained in Article 97 to Article 120 of Act 32/2009.